Scaffolding pada Pengajaran Bahasa Inggris di SMP Kanisius St. Yoris Semarang - Suwarti, Tarcisia Sri; Lestari, Siti; Widiyanto, M. Wahyu (Media Penelitian Pendidikan : Jurnal Penelitian dalam Bidang Pendidikan dan Pengajaran, 2024)
Junior high school education is an advanced stage of mastering English. However, students' levels of ability to receive and master the material differ from each other. Teachers need to apply better learning methods so that students can develop according to their educational level, one of the methods is scaffolding method. The problem studied refers to the problem formulation as follows: 1) How do teachers use scaffolding in teaching English at Kanisius St. Yoris Junior High School Semarang? 2) What types of scaffolding do the teachers use? 3) Why do teachers use scaffolding teaching techniques with their students? This research method is a qualitative descriptive method. The research subjects are St. Yoris Kanisius Junior High School teachers. The stages of the research method are through data collection (observation, questionnaires and interviews), data classification and data analysis carried out directly at St. Yoris Kanisius Junior High School Semarang. The conclusions of this research are: 1) Teachers use scaffolding in teaching English at St. Yoris Kanisius Junior High School Semarang during pre activity, main activity and post activity; 2) The types of scaffolding applied are scaffolding down and scaffolding up; 3) Teachers use scaffolding teaching techniques to their students because scaffolding creates a supportive learning environment, helps reduce boredom and increase student activity, and reduces tension so that the material presented can be received and absorbed well by students.